Study on Tax Expenditures in Pakistan - Ahmed, Ather Maqsood; Ather, Robina (World Bank, Washington, DC, 2014)
The problems of high fiscal deficit, high current account deficit, and high inflation faced by the government of Pakistan are linked to Pakistan's weak tax revenue effort. There are concerns that revenue in Pakistan is raised in an inefficient way by favoring certain sectors and economic activities over others. The assessment of tax expenditures is often complicated because reporting and accounting practices fall far short of what is used for official government expenditures, which makes it difficult, if not impossible, to evaluate the cost, efficiency and distributional impact of tax expenditures. The purpose of the study is to undertake a detailed assessment of tax expenditure in Pakistan, including an appropriate definition and methodologies for measuring tax expenditures. Considerable effort is required to develop and establish a suitable framework to identify, measure and critically assess the merits of tax expenditures on an annual basis. Pakistan is committed to increasing the transparency of tax policy by providing detailed estimates of tax expenditures. This paper provides a detailed assessment of tax expenditures in Pakistan, framework, and a methodology for measuring tax expenditures.